2014
DOI: 10.4161/hv.35119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of virulence between theYersinia pestis Microtus201, an avirulent strain to humans, and the vaccine strain EV in rhesus macaques,Macaca mulatta

Abstract: Our previous study has demonstrated that Yersinia pestis Microtus 201 is a low virulent strain to the Chinese-origin rhesus macaques, Macaca mulatta, and can protect it against high dose of virulent Y. pestis challenge by subcutaneous route. To investigate whether the Y. pestis Microtus 201 can be used as a live attenuated vaccine candidate, in this study its intravenous virulence was determined and compared with the live attenuated vaccine strain EV in the Chinese-origin rhesus macaque model. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Non-human primates are the best and most accurate animal model of human infection [85][86][87][88][89][90][91][92][93] and are often used in preclinical trials [122]. Similar to companion animals, non-human primates are also USDA protected, although the approvals and protocol requirements differ.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-human primates are the best and most accurate animal model of human infection [85][86][87][88][89][90][91][92][93] and are often used in preclinical trials [122]. Similar to companion animals, non-human primates are also USDA protected, although the approvals and protocol requirements differ.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Vaccination studies are commonly done in mice [40,42,49], rabbits [65,66], cattle [81], and primates [86,91,93]. These studies can demonstrate the power of inhibiting the T3SS by using antibodies that recognize T3SS effectors or structural components.…”
Section: Vaccines and Immunizationsmentioning
confidence: 99%
“…Y. pestis strain 201, which is avirulent to humans ( 53 ), is maintained in our laboratory. It was cultivated in Brain Heart Infusion broth (BHI; BD, Voigt Global Distribution Inc., Lawrence, KS).…”
Section: Methodsmentioning
confidence: 99%
“…rhesus macaque infection model revealed that both strains were well tolerated in NHPs at high doses. However, the microtus strain infected the lungs and led to 100% mortality in 10 10 i.v.-challenged animals; none of the EV-challenged animals died at that same dose (Tian et al 2014 ). The side effects associated with the EV strain in humans as well as the ability of the pigmentation locus (pgm) minus strains of Y. pestis to cause a fatal disease in patients with hemochromatosis suggest that the EV mutant strain could be further attenuated through specific gene knockouts to generate live-attenuated plague vaccine candidates, as has been recently reported (Tiner et al 2015A &B; Tiner et al 2016 ; van Lier et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%